Learning Innovations in Improving Arabic Speaking Proficiency for Adult Learners : Literature Review - Alamin, Fajar; Sopian, Asep; Japakiya, Rusdee (Lughawiyah: Journal of Arabic Education and Linguistics, 2024)
This study aims to identify innovations in Arabic language learning for speaking proficiency among adult learners over the past 10 years. The method used is a Systematic Literature Review (SLR) with databases Scopus, Emerald, Science Direct, and Google Scholar. From the initial 1725 articles, 28 relevant articles were screened using Covidence and the PRISMA method. The results show innovations in models, methods, approaches, media use, teaching material development, and assessment systems, with most yielding positive outcomes. These innovations can be implemented in other institutions or tested in different contexts. However, some negative results, especially in khitobah practice, were due to insufficient supervision or the ineffectiveness of the practice. Several articles did not report the outcomes of the innovations, presenting opportunities for further research to evaluate these innovations more deeply.